Penerapan Data Mining Untuk Memprediksi Hasil Produksi Buah Kelapa Sawit Pada PT.LNK Kebun Basilam Menggunakan Algoritma C5.0 - Elvira Hanum Nst; Rismayanti; Yuyun Dwi Lestari (Universitas Harapan Medan, 2021)
PT. LNK Basilam Gardens is a large private plantation located in BasilamGardensLangkat Regency. Every year this company has problems in predicting the yield of oil palm fruit production. Improper production results areoneofthe cause of errors in policy making. The planning that is done sometimes still gives less than optimal results. This is because the calculation process is still using manual analysis. The prediction technique used is the C5.0 algorithm learning method. This method has the advantage of dealing with problems such as missing values ??and large amounts of data. This algorithm can also do data training in a fast time for use in testing data.